P-cadherin-mediated Rho GTPase regulation during collective cell migration - Plutoni, Cédric (Small GTPases, 2016)
This commentary addresses the role of P-cadherin in collective cell migration (CCM), a cooperative and coordinated migration mode, used by cells during normal and pathological migration processes. We discuss how cadherin-mediated cell-cell junctions (CCJs) play a critical role in CCM through their ability to regulate Rho GTPase-dependent pathways and how this leads to the generation and orientation of mechanical forces. We will also highlight the key function of P-cadherin (a poor prognostic marker in several tumors) in promoting collective cell movement in epithelial and mesenchymal cells.